Pengaruh Pengetahuan Pasar Modal, Motivasi, Return Investasi dan Resiko Terhadap Minat Investasi di Pasar Modal - Christina Ramadani Br Hasibuan; Tetty Tiurma Uli Sipahutar; Eunike Christina Simbolon; Ria Manurung (Owner : Riset dan Jurnal Akuntansi, 2023)
The purpose of this study is to examine Capital Market Knowledge, Motivation, Return on Investment, and Risk affect investment interest. The sampling technique used is purposive sampling. In this study, the population used was 200 millennial generation respondents such as students or business people who were born in 1982-2003 in the city of Medan. There were 133 samples that met these characteristics. This study used a quantitative method where researchers distributed questionnaires to be filled out by respondents with the help of the SPSS test tool. Multiple linear analysis is used in data analysis methods. Analytical tests used include normality tests, multicollinearity tests, reliability tests, validity tests, and classical assumption tests. The results of the study show: 1) Investment interest has a positive effect on capital market knowledge (X1), with a regression coefficient of 0.212; 2) A positive relationship between investment interest and motivation (X2) with a regression coefficient of 0.108; 3) A positive relationship between investment interest and investment return (X3), with a regression coefficient of 0.369; 4) A positive relationship between investment interest and risk (X4) which has a regression coefficient of 0.126. Investment interest is influenced by capital market knowledge and investment returns. Investment interest is not influenced by motivation and risk.